Interspecific plastidial recombination in the diatom genus Pseudo‐nitzschia. Issue 6 (23rd October 2015) - D'Alelio, Domenico; Ruggiero, Maria Valeria
Abstract : Plastids are usually uni‐parentally inherited and genetic recombination between these organelles is seldom observed. The genus Pseudo‐nitzschia, a globally relevant marine diatom, features bi‐parental plastid inheritance in the course of sexual reproduction. This observation inspired the recombination detection we pursued in this paper over a ~1, 400‐nucleotide‐long region of the plastidial rbc L, a marker used in both molecular taxonomy and phylogenetic studies in diatoms. Among all the rbc L‐sequences available in web‐databases for Pseudo‐nitzschia, 42 haplotypes were identified and grouped in five clusters by Bayesian phylogeny. Signs of hybridization were evident in four of five clusters, at both intra‐ and interspecific levels, suggesting that, in diatoms, (i) plastidial recombination is not absent and (ii) hybridization can play a role in speciation of Pseudo‐nitzschia spp.